High NPHP1 and NPHP6 Mutation Rate in Patients with Joubert Syndrome and Nephronophthisis: Potential Epistatic Effect of NPHP6 and AHI1 Mutations in Patients with NPHP1 Mutations - Tory, Ka[Combining Acute Accent]lma[Combining Acute Accent]n; Lacoste, Tiphanie; Burglen, Lydie; Morinie[Combining Grave Accent]re, Vincent; Boddaert, Nathalie; Macher, Marie-Alice; Llanas, Brigitte; Nivet, Hubert; Bensman, Albert; Niaudet, Patrick; Antignac, Corinne; Salomon, Re[Combining Acute Accent]mi; et al. (Journal of the American Society of Nephrology, 2007)
Joubert syndrome (JS) is an autosomal recessive disorder that is described in patients with cerebellar ataxia, mental retardation, hypotonia, and neonatal respiratory dysregulation. Kidney involvement (nephronophthisis or cystic renal dysplasia) is associated with JS in one fourth of known cases. Mutations in three genes--AHI1, NPHP1, and NPHP6--have been identified in patients with JS. However, because NPHP1 mutations usually cause isolated nephronophthisis, the factors that predispose to the development of neurologic involvement are poorly understood. In an attempt to identify such genetic determinants, a cohort of 28 families with nephronophthisis and at least one JS-related neurologic symptom were screened for mutations in AHI1, NPHP1, and NPHP6 genes. NPHP1 and NPHP6 homozygous or compound heterozygous mutations were found in 13 (46%) and six (21%) unrelated patients, respectively. Two of the 13 patients with NPHP1 mutations carried either a heterozygous truncating mutation in NPHP6 or a heterozygous missense mutation in AHI1. Furthermore, five patients with NPHP1 mutations carried the AHI1 variant R830W, which was predicted to be "possibly damaging" and was found with significantly higher frequency than in healthy control subjects and in patients with NPHP1 mutations without neurologic symptoms (five of 26 versus four of 276 and three of 152 alleles; P < 0.001 and P < 0.002, respectively). In contrast to the variable neurologic and milder retinal phenotype of patients with NPHP1 mutations, patients with NPHP6 mutations presented with a more severe neurologic and retinal phenotype. In conclusion, NPHP1 and NPHP6 are major genes of nephronophthisis associated with JS. Epistatic effects that are provided by heterozygous NPHP6 and AHI1 mutations and variants may contribute to the appearance of extrarenal symptoms in patients with NPHP1 mutations.